New t‐butyl based aspartate protecting groups preventing aspartimide formation in Fmoc SPPS. (15th June 2015) - Behrendt, Raymond; Huber, Simon; Martí, Roger; White, Peter
<x xml:space="preserve">Abstract</x> Obtaining homogenous aspartyl‐containing peptides via Fmoc/tBu chemistry is often an insurmountable obstacle. A generic solution for this issue utilising an optimised side‐chain protection strategy that minimises aspartimide formation would therefore be most desirable. To this end, we developed the following new derivatives: Fmoc‐Asp(OEpe)‐OH (Epe = 3‐ethyl‐3‐pentyl), Fmoc‐Asp(OPhp)‐OH (Php = 4‐n‐propyl‐4‐heptyl) and Fmoc‐Asp(OBno)‐OH (Bno = 5‐n‐butyl‐5‐nonyl). We have compared their effectiveness against that of Fmoc‐Asp(OtBu)‐OH and Fmoc‐Asp(OMpe)‐OH in the well‐established scorpion toxin II model peptide variants H‐Val‐Lys‐Asp‐Asn/Arg‐Tyr‐Ile‐OH by treatments of the peptidyl resins with the Fmoc removal reagents containing piperidine and DBU at both room and elevated temperatures. The new derivatives proved to be extremely effective in minimising aspartimide by‐products in each application. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.